The effect of sales promotion and hedonic shopping motivation on impulse buying in resso applications - Leo Abdul Azis; Citra Savitri; Syifa Pramudita Faddila (International Journal of Applied Finance and Business Studies, 2022)
Current buying behavior has changed, where many people make unplanned purchases. This study aims to determine: Partial influence of Sales Promotion on Impulse Buying, Partial influence of Hedonic Shopping Motivation on Impulse Buying. This research was conducted at the University of Buana Perjuangan Karawang for Management students of the 2018-2021 class. The type of research used is quantitative research, using a sample of 100. The sampling technique used was the Lemeshow technique. The data collection method used in this research is to take notes on quantitative research using a questionnaire. Data analysis is SEM (Structural Equation Model) based on PLS (Partial Least Square). The results show that: There is a partially significant effect of Sales Promotion on Impulse Buying with T-Statistics of 2.886, there is a partially significant effect of Hedonic Shopping Motivation on Impulse Buying with T-Statistics of 6.274, both of which are greater than the significance used, namely 1, 96 so that it can be stated that sales promotion and Hedonic Shopping Motivation variables have a positive effect on Impulse Buying. The sales promotion variable on impulse buying shows a positive and significant direct relationship. The hedonic shopping motivation variable on impulse buying shows a positive and significant direct relationship.